Akhir Zaman: Representasi Fenomena Alam dan Sosial melalui Komposisi Kacapi - Yulaeliah, Ela (Resital: Jurnal Seni Pertunjukan, 2023)
ABSTRACTThe End of Time: Representations of Natural and Social Phenomena through Kacapi Kawih Composition. The objective of this study is to analyze the results of a composition entitled End Times as a representation of natural and social phenomena. The method proposed by Alma W. Hawkins used in the process of creating this work include exploration, improvisation, and formation. The work entitled End Times is inspired by various natural and social phenomena that occur in society, such as volcanic eruption, flood, tsunami, and even covid-19 that boomed recently. Furthermore, the social order of society is increasingly uncertain due to war, assassination, and even oppression by the powerful over the weak. These are signs or characteristics of the end of time related to the involvement of mankind in nature. These various phenomena are the source of creativity and inspire the author to create a fresh work in the composition of the Sundanese kacapi kawih entitled "The End of Time". This composition attempts to construct an atmosphere of silence, emotion, comfort as well as anxiety through the Sundanese musical concepts and elements (rhythmic, melodic, ornamentation, dynamics, and other musical interweaving). In this study, the author used kacapi instruments, flutes, and song lyrics in which the song lyrics were carried through vocals. Since the lyrics are means of conveying moral messages to the public, they are considered as the prominent priority in this composition. The result indicates that the composition work entitled "The End of Time" has succeeded in conveying moral messages about the characteristics of the world’s end of time (apocalypse) to the public through the various phenomena reflected in performances and publications in online media. This art work is a wholesome reminder of moral values that have been eroded recently and encourages people to realize the true purpose of life.ABSTRAKTujuan penulisan ini untuk menganalisis hasil komposisi berjudul Akhir Zaman sebagai representasi dari fenomena alam dan sosial. Metode Alma W. Hawkins digunakan dalam proses penciptaan karya ini meliputi eksplorasi, improvisasi, dan pembentukan. Karya berjudul Akhir Zaman terinspirasi oleh berbagai fenomena alam dan sosial yang terjadi di masyarakat dunia. Dunia sudah dianggap tua dan rapuh, sehingga sering terjadi bencana di mana-mana, seperti gunung meletus, banjir, sunami, bahkan covid-19 yang terjadi bau-baru ini. Begitu pula tatanan sosial masyarakat dunia semakin tidak menentu dengan terjadi perang di mana-mana, pembunuhan, bahkan penindasan oleh orang yang berkuasa terhadap orang yang lemah. Inilah sebagai tanda atau ciri-ciri akhir zaman yang penuh gejolak dengan keterlibatan umat manusia beserta alam lingkungannya. Berbagai fenomena tersebut menjadi inspirasi pengkarya untuk membuat karya baru serta dijadikan sumber ide penciptaan dalam komposisi kacapi kawih Sunda berjudul “Akhir Zaman”. Komposisi ini mencoba membangun suasana hening, haru, hidmat namun was-was yang dibangun melalui konsep musikal Sunda dan unsur-unsurnya (ritmis, melodi, ornamentasi, dinamika, serta jalinan musikal lainnya) dengan instrumen kacapi, suling, dan lirik lagu. Lirik lagu melalui vokal bertujuan agar pesan moral dapat tersampaikan ke publik. Kekuatan lirik lagu merupakan prioritas utama dalam komposisi ini untuk menyampaikan pesan pengkarya. Hasil kesimpulan menunjukkan bahwa karya komposisi berjudul Akhir Zaman telah berhasil menyampaikan pesan moral tentang ciri-ciri akhir zaman (kiamat) kepada publik dengan berbagai fenomenanya yang disampaikan melalui pertunjukan serta publikasi di media online. Hasil karya ini bermanfaat bagi pengingat nilai-nilai moralitas yang sudah tergerus akhir-akhir ini untuk lebih menyadarkan tujuan hidup yang sebenarnya.